ANALISIS PENGARUH FAKTOR FUNDAMENTAL TERHADAP RETURN SAHAM STUDI KASUS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK JAKARTA PERIODE 1998 - 2001 - Kusumawati, Rita Kusumawati; Susilowati, Firti Susilowati (Universitas Muhammadiyah Magelang, 2004)
This research is aimed at analizing influence of fundamental factors on stock return of manufactur industries. The research result show that from the five factors (Debt to Equity Ratio, Devidend Payout Ratio, Earning Per Share, Net Profit Margin, Return Asset) assumed to influence on stock return of manufactur industries under investigation, there are five factor which simultan show significant influence stok return. However, only Earning Per Share which partially show significant influence stock return. And Earning Per Share as a dominant factor in influencing stock return. Based onthe research result, it is also discovered that fundamental factor (Debt to Equity Ratio, Dividend Payout Ratio, Earning Per Share, Net Profit Margin, Return Asset) have weak influence in explaning stock return variation at the Indonesian Capital Market, in which Adj.R- Square is 27,0%. This indicates that Indonesian investors can't created the factor fundamental as basic judgment to get stock return, with pay attention ekstern factors, like as: interest rate, inflation, exchange rate kurs, political condition, etc.